If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + 3(x + 4) = -2 Reorder the terms: 22 + 3(4 + x) = -2 22 + (4 * 3 + x * 3) = -2 22 + (12 + 3x) = -2 Combine like terms: 22 + 12 = 34 34 + 3x = -2 Solving 34 + 3x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + 3x = -2 + -34 Combine like terms: 34 + -34 = 0 0 + 3x = -2 + -34 3x = -2 + -34 Combine like terms: -2 + -34 = -36 3x = -36 Divide each side by '3'. x = -12 Simplifying x = -12
| 4-(x+3)=2(x+3)+6 | | -1z-1(z-6)=8 | | 3(x-4)+1=19 | | 10x+10x=6x+8+6x+8 | | 2x(7x-10)=0 | | 2n+3=6n+31 | | 6a=0.24 | | 3x+3x=5x-8+5x-8 | | 4.4=-2+4 | | -4.05x+-2500=0 | | 99=5x+9 | | -4.05x+-2500=-3000 | | 3x-4+1=19 | | 49=3.5x | | x-19=57 | | 3(x+4)-6=30 | | 16.38=2s+4.12 | | 3t-(-2t)+14=6 | | 5.1=8.1 | | c+6=7 | | -5.4q=-11.1-1.7q | | 576x^2-1824x+1369=0 | | 2(x+1)=x+4 | | 3x^2+2x=-12 | | 9x+y+11=16 | | ln(2x-5)=10 | | 4-(x-3)=2(x+3)+6 | | 4[x-7]+13=27 | | 27.5+n=87.8 | | 3x^2+2=-12 | | x^19=57 | | 2(3y+5)=6y+10 |